VD_FINDINFO Arrêt / 2025 / 249 vom 18. Juni 2025 - VD Tribunal cantonal (2025)
PRESTATION D'ASSURANCEAM, ASSURANCE-MALADIE ET ACCIDENTS, TRAITEMENT À L'ÉTRANGER, TRANSSEXUALISME | 24 LAMal, 25 LAMal, 32 al. 1 LAMal, 34 al. 2 LAMal, 36 al. 1 OAMal, 36 al. 2 OAMal, 36 OAMal